2007
DOI: 10.1097/01.nnr.0000270031.64810.0c
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model for Osteoporosis Preventing Behavior in Postmenopausal Women

Abstract: Personal knowledge of DXA results was related significantly to increases in calcium intake in postmenopausal women, but not to exercise. Directions for further study are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 24 publications
7
47
1
3
Order By: Relevance
“…This finding was in line with that of Estok et al (2007) and Swaim et al (2008) who found self-efficacy explained 16% and 13% of the variance in weight bearing physic activity in postmenopausal women, respectively. Additionally, other researchers have studied factors that tend to impede physical activity in middle to older-aged women (i.e.…”
Section: Mvpa Minutes Per Daysupporting
confidence: 81%
See 4 more Smart Citations
“…This finding was in line with that of Estok et al (2007) and Swaim et al (2008) who found self-efficacy explained 16% and 13% of the variance in weight bearing physic activity in postmenopausal women, respectively. Additionally, other researchers have studied factors that tend to impede physical activity in middle to older-aged women (i.e.…”
Section: Mvpa Minutes Per Daysupporting
confidence: 81%
“…This study indicates the importance of self-efficacy for physical activity performed for OP prevention. Similar findings were also found in a recent investigation by Estok, Sedlak, Doheny, and Hall (2007) who reported task selfefficacy for exercise was significantly related to weight bearing physical activity (r = 0.41). These studies emphasize the importance of task self-efficacy for performance of the type of physical activity (weight-bearing) that is important for bone health.…”
Section: Individual Psychological Determinantssupporting
confidence: 77%
See 3 more Smart Citations